Taking Stock: The Evolution of Archival Science in Québec - Couture, Carol (Archivaria, 2005)
The author looks back over the past thirty years of archival science in Québec, identifying seven milestone events which have marked its development: the creation of l’Association des archivistes du Québec (AAQ) in 1967; the Manuscript Affair in 1972; the Jean-Paul L’Allier Cultural Policy of 1976; Québec’s 1982 Act respecting Access to Documents held by Public Bodies and the Protection of Personal Information and the 1983 Archives Act; the creation of university archival education programs beginning in 1983; the creation of the Canadian Council of Archives in 1985; and the XIIth International Congress on Archives, held in Montréal in 1992. The author demonstrates that each of these events contributed elements essential to the creation of the discipline, and that in the past thirty years archival science in Québec has developed its own unique character, responds to the needs and expectations of Québec society, and continues to evolve. RÉSUMÉ Dans ce texte l’auteur retrace les trente dernières années de l’archivistique québécoise en identifiant sept événements-jalons qui ont marqué le développement de la discipline au Québec : la création de l’Association des archivistes du Québec (AAQ) en 1967; l’Affaire des manuscrits en 1972; la politique culturelle de Jean-Paul L’Allier en 1976; la mise en place de la Loi sur l’accès aux documents des organismes publics et sur la protection des renseignements personnels (1982) et la Loi sur les archives (1983); la mise en place de programmes de formation dans les universités à compter de 1983; la création du Conseil canadien des archives (CCA) en 1985; et la tenue du XIIe Congrès international des archives à Montréal en 1992. L’auteur démontre que chacun des ces événements a produit des éléments essentiels à la création d’une discipline en tant que telle, et qu’au bout de trente ans, l’archivistique québécoise a su se distinguer des autres, répond aux attentes de la société et continue d’évoluer.